Salmon aquaculture waste effects on the distribution of epibenthic invertebrates and demersal fish and subsequent impacts on Atlantic cod dietary items - Markussen, Kari Branem (UiT The Arctic University of Norway, 2022)
Open-cage fish farms are common structures in coastal waters and are known to attract wild fish. Environmental impacts from the farming of Atlantic salmon, Salmo salar, create concerns related to further growth of the industry. Uneaten feed pellets and faeces that are discharged from the farms leads to changes in the environments under and around the farm facilities. Sedimentation due to farm enrichment affects the organisms living on and within the sediments. This study characterizes the benthic epifaunal invertebrate and the demersal fish communities in relation to the distance from a fish farm in a fjord with hard and mixed bottom substrates in Northern Norway. A towed underwater video system was used to quantitatively assess the densities of epibenthic fauna and demersal fish species along 9 transects near the farm and 8 reference transects at greater distance to the farm. This study found that salmon aquaculture had moderate effects on the epifaunal invertebrate and demersal fish community composition in the fjord. An aggregation of flatfish species, that are known to feed on infaunal polychaetes, was observed within 500 m of the farm, where opportunistic polychaetae accumulations are abundant due to organic farm waste. Data on the diet of coastal Atlantic cod, Gadus morhua, caught in the same fjord, was used to compare the distribution of dietary items of cod observed in the video transects to the diet of cod caught 0-50 m from the farm and over 2 km from the farm. There was no strong overlap between the diet of cod caught in the area and the epifauna observed, but there was an interesting pattern in epifaunal distribution of the Atlantic cod dietary items. Blue mussel, Mytilus edilus, urchin, Echinoidea, crabs of the family Lithodidae, American plaice, H. platessoides, and the tunicates and sea squirts of the class Ascidians, all changed in their distribution along the enrichment gradient from the farm, and were all found to be attracted to the area within 500 m from of the farm. Further research needs to ...